Unusual recurrent rectal carcinoma: A cancer field theory viewpoint - Vyslouzil, Kamil; Brychtova, Svetlana; Zboril, Pavel; Skalicky, Pavel; Vomackova, Katherine; Bezdekova, Michala; Brychta, Tomas (Biomedical papers, 2014)
Aim: The rate of rectal cancer locoregional recurrence following radical surgery varies from 4% to 33%. Though the causes are unclear, likely factors include microscopic tumor residues in the lymphatics, positive resection margins and exfoliation of tumor cells and their subsequent intraluminar spread during operation. Other significant factors include type and technique of surgical procedure. Recently, it has been demonstrated that local recurrence may also be associated with the biological behaviour of the tumor and/or with the composition of the cellular microenvironment which creates optimal conditions for the growth and spread of tumor cells.Case report: The presented case here is interesting because the tumour recurred early following a curative surgical procedure with negative resection margins, without positive lymph nodes, without infiltration of the pelvic wall and without distant metastases.Conclusion: In patients with a determined risk of genetically altered tumor field encompassing epithelial or stromal changes, a different treatment strategy, including gene therapy, anti-inflammatory or anti-angiogenic therapy should be chosen to minimize increased tumor risk.
Keywords: rectal cancer; recurrence; cellular microenvironment